Synthesis and Magnetic Properties of M (Mg, Mn, Ni and Zn) Doped CuO Ceramics - Yang, S.H. (Asian Journal of Chemistry, 2011)
MxCu1-xO (M = Mg, Mn, Ni and Zn, x = 0.04) ceramics were synthesized using traditional ceramic product method. Crystal structures of all the samples were studied by X-ray diffraction, from which we can see that all the samples were well crystallized. Field dependences of magnetization and temperature dependences of magnetization were performed on a superconducting quantum interference device (SQUID) at 5 K with the applied of 5 T and in the range from 5 K to 300 K, respectively. Both M-T and M-H results implied the ferromagnetic behaviour of Mn and Mg doped CuO samples. Meanwhile Ni and Zn doped CuO samples still showed antiferromagnetic behaviour with the transition temperature at ca. 230 K. The only effects brought by Ni and Zn doping were the increase of magnetization of CuO. Through comparing of the different magnetic behaviours, we discussed the mechanism of ferromagnetism observed in Mn and Mg doped CuO samples.